Crenças em saúde, Teoria da Ação Planejada e saúde do homem : predizendo a intenção de realização do exame do toque retal - Turri, Geovanna Santana de Souza (2017)
The present dissertation aimed to investigate beliefs and other constructs of the Theory of Planned Behavior (TPB), to developing a model able to identifying the main predictors of the intention to perform Digital Rectal Exam (DRE). For this, we did three studies. In the Study 1, a theoretical chapter on TAP and its applicability to human health behaviors was carried out, with emphasis on the behavior of the ETR. The Studies 2 and 3 were empirical, men between 40 and 70 years old participated, dividing them into two groups: the men that did the DRE x the men that didn’t do the DRE. In the Study 2, we aimed to identify the main beliefs of men about DRE, comparing the responses pattern by group. Here, a questionnaire with sociodemographic and clinical questions and the free word evocation technique were used. We found that men who had already done DRE tended to evoke more terms for the susceptibility and severity of prostate cancer, while men who had never done emphasized the susceptibility to cancer and also the benefits of doing the DRE. These data showed how each group looks at the DRE, allowing for occasional interventions. The Study 3 investigated the predictive model of TPB (attitudes, norms and perception of control), aiming to identify the main predictors of the intention to doing the DRE. A scale with TPB constructs was used, as well as sociodemographic and clinical issues. In short, the results revealed that the attitude is better to predict the intent of men who had never done the DRE, while the norms are better to predict the intention of men who had already done so. And the perception of control seemed to work with the male audience whatever if they did or not the exam. Finally, we understood that TPB and the study of beliefs can help social and health researchers to understand the single factors that induce a person to engage in the behavior of interest, in this case, to understand how men engage in the DRE.